Letters to the lost - Grey, Iona (Thomas Dunne Books, St. Martin's Press, 2015)
Late on a frozen February evening, a young woman is running through the streets of London. Having fled from her abusive boyfriend and with nowhere to go, Jess stumbles onto a forgotten lane where a small, clearly unlived in old house offers her best chance of shelter for the night. The next morning, a mysterious letter arrives and when she can't help but open it, she finds herself drawn inexorably into the story of two lovers from another time. Fate is unkind and they are separated by decades and continents. In the present, Jess becomes determined to find out what happened to them. Her hope--inspired by a love so powerful it spans a lifetime--will lead her to find a startling redemption in her own life.